Evaluation of Electronic MedicalRecords (SIMPUS) at ABC XYZ Community Health Center Using the EUCS Method - Berkah Putri Lefesi (Gayaku Publisher, 2025)
The Health Center Information System (SIMPUS) as an electronic medical record platform is a key instrument in realizing the digitalization of primary health services in Indonesia. However, implementation without proper evaluation risks resulting in systems that do not meet user needs. This study evaluates user satisfaction with the electronic medical records (SIMPUS) at Puskesmas ABC, XYZ Regency, YYY Province using the End User Computing Satisfaction (EUCS) method. The research employs a descriptive quantitative approach with a cross-sectional design. Respondents consisted of 52 health workers who actively use SIMPUS, selected using total sampling. Data were collected through a structured questionnaire adapted from the EUCS instrument covering five dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. Validity and reliability tests were conducted before data collection. Data analysis used descriptive statistics and gap analysis between expectations and perceptions. Results show an overall user satisfaction index of 72.6% (Good category). The highest satisfaction was found in the Accuracy dimension (75.8%) and the lowest in the Ease of Use dimension (67.4%). Gap analysis reveals the largest negative gap in Ease of Use (gap score: −0.74), indicating that system ease of use is the most critical aspect requiring improvement. The novelty of this research lies in the application of gap analysis between user expectations and actualperceptions as an enrichment of the standard EUCS method, providing deeper diagnostic information for system improvement recommendations that are more targeted and actionable specifically for SIMPUS in the Puskesmas context.